Intelligently designed : how creationists built the campaign against evolution - Caudill, Edward (Urbana, Chicago, and Springfield : University of Illinois Press, 2013)
" Tracing the growth of creationism in America as a political movement, this book explains why the particularly American phenomenon of anti-evolution has succeeded as a popular belief. Conceptualizing the history of creationism as a strategic public relations campaign, Edward Caudill examines why this movement has captured the imagination of the American public, from the explosive Scopes trial of 1925 to today's heated battles over public school curricula. Caudill shows how creationists have appealed to cultural values such as individual rights and admiration of the rebel spirit, thus spinning creationism as a viable, even preferable, alternative to evolution. In particular, Caudill argues that the current anti-evolution campaign follows a template created by Clarence Darrow and William Jennings Bryan, the Scopes trial's primary combatants. Their celebrity status and dexterity with the press prefigured the Moral Majority's 1980s media blitz, more recent staunchly creationist politicians such as Sarah Palin and Mike Huckabee, and creationists' savvy use of the Internet and museums to publicize their cause. Drawing from trial transcripts, media sources, films, and archival documents, Intelligently Designed highlights the importance of historical myth in popular culture, religion, and politics and situates this nearly century-old debate in American cultural history. "--
"Tracing the growth of creationism in America as a political movement as opposed to a science-religion issue, this book explains why anti-evolution, this peculiarly American phenomenon, has succeeded, as measured in terms of popular appeal. Conceiving the history of creationism as a strategic public relations campaign, it emphasizes ways that media have been used to spin creationism as a viable, even preferable, alternative to evolution. Understanding creationists' campaigns means understanding their popularity and appeal in American culture. Beginning with the rise of fundamentalism in the early 20th century, Edward Caudill traces the movement through the rest of the 20th and into the 21st century. He illustrates how the 1925 Scopes trial created the contours of the modern debate over evolution. Its primary combatants--Clarence Darrow and William Jennings Bryan--became the celebrity representatives of opposing sides in the battle over teaching evolution in public schools. He then draws parallels between the media's role in the Scopes trial and subsequent political campaigns against evolution represented by Moral Majority of the 1980s, the 2005 cases in Kansas and Dover, PA, current anti-evolution politicians, such as Sara Palin and Mike Huckabee, and highlight creationism's recent gravitation toward museums and websites as a medium of communication. Caudill draws from media sources, trial transcripts, films, as well as the archives to highlight the importance of historical myth in popular culture, religion, and politics and situate this nearly century-old debate in American cultural history"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: Creationism -- United States -- History; Evolution (Biology) -- Religious aspects -- Christianity -- History; Intelligent design (Teleology) -- History; United States -- Church history -- 20th century; SOCIAL SCIENCE / Media Studies; SCIENCE / Life Sciences / Evolution; RELIGION / Christian Theology / General; Electronic books